Admissions and transfers from a rural emergency department. - De Freitas, T. L. (College of Family Physicians of Canada, 1998)
OBJECTIVE: To examine the characteristics of patients transferred from a rural hospital emergency department, to compare them with patients admitted on an emergency basis, and to use this information to help plan physician education. DESIGN: Descriptive study using records for the period January 1, 1991, to June 30, 1992. SETTING: The emergency department at Bonnyville Health Centre, an acute care rural hospital located 240 km northeast of Edmonton, serving a catchment population of approximately 10,000. PARTICIPANTS: One thousand fifty-five patients seen in the emergency department who were either transferred to another centre or admitted to the Bonnyville Health Centre on an emergency basis. MAIN OUTCOME MEASURES: For the transferred group, main diagnosis, category of transfer, and reason for transfer. For the admitted group, main diagnosis, length of stay, type of discharge. RESULTS: Of the 1055 patients ill enough to be either admitted or transferred, 114 (10.8%) were transferred. Those transferred were predominantly men, the elderly, and people with orthopedic injuries or neurologic diseases. Those admitted presented primarily with internal, respiratory, gynecologic, or pediatric disorders. Reason for transfer was mainly lack of specialized services or equipment at the rural hospital. CONCLUSIONS: Patients transferred out of the emergency department differed from those admitted in diagnoses and sex. Most transfers were considered "mandatory." Results of this analysis supported incorporating a formal rotation in orthopedics and adding 4 weeks to the existing emergency medicine rotation in our family medicine residency program.